A Placebo-Controlled Study on the Treatment of Metabolic Syndrome of Qi Stagnation and Dampness Obstruction Related to Atypical Antipsychotics with Traditional Chinese Medicine (TCM). (30th July 2020) - Sun, Fengli; Ren, Zhibin; Jiang, Yonghong; Fang, Xiangming; Wang, Naixin; Jin, Weidong
Abstract : Backgroud . To observe the effects of Liuyu decoction on qi stagnation and dampness obstruction syndrome of metabolic syndrome related to atypical antipsychotics . Methods . 154 schizophrenics who met both the diagnostic criteria of metabolic syndrome and qi stagnation and dampness obstruction syndrome were randomly divided into 2 : 1 groups. The PANSS and Tess were assessed before treatment and at the end of first month, second month, and third month after treatment; blood pressure, weight, waist circumference, hip circumference, blood glucose, glycosylated hemoglobin, high-density lipoprotein, low-density lipoprotein, triglyceride, and cholesterol were also measured at the same four time points. On the basis of continuous antipsychotic treatment, the study group took Liuyu decoction, and the control group took placebo. Results . Of the 154 cases, 102 were in the study group and 52 in the control group. Before and after treatment, there was a slight increase but no significant difference in blood pressure, blood sugar, glycosylated hemoglobin, cholesterol, TG, DHL, and LHL in two groups (P > 0.05 ) and also between the two groups (P > 0.05 ). The body weight, waist circumference, hip circumference, and BMI in the study group decreased, while that in the control group increased from the dividing group to the end of study. At the end of the third month, there was a significant difference in the body weight, waist circumference, hip circumference, and BMI between the two groups (P < 0.05 ). Before and after treatment, there was a significant difference in positive symptoms, negative symptoms, general symptoms, and PANSS in two groups, respectively (P < 0.05 ). The negative symptoms, general symptoms, PANSS, and TESS in the study group were lighter than that in the control group after treatment. Conclusion . Liuyu decoction is not only beneficial to the treatment in body constitution of metabolic syndrome in qi stagnation and dampness obstruction but also beneficial to the improvement of such patients' mental symptoms and side effects.